2021
DOI: 10.3390/vaccines9050494
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Level of Antibodies to Measles Virus in Adults

Abstract: Individuals without a protective antibody level are susceptible to measles infection. There are differences in the persistence of antibodies after vaccination and infection, while the impact of gender on this process has not been sufficiently studied. Measles Ig G antibodies were measured in 1742 employees of a large hospital facility—403 men and 1339 women aged from 25 to 67 years; 15% participants had antibody levels less than the protective threshold of ≥0.18 IU/mL. Significant differences were found in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…Comparing the levels of antibody concentrations among sexes, males seem to present higher concentrations, but this is not statistically significant and comes in contrast with the general acceptance that females typically develop higher immune responses to viral infections and vaccines [ 42 ]. However, comparing the concentrations among sexes per age group, males presented statistically significantly higher concentration in the younger age group “25–54”, a finding also supported by another study [ 43 ]. In any case, both sexes showed high antibody concentrations in all age groups, making them immune to measles.…”
Section: Discussionsupporting
confidence: 81%
“…Comparing the levels of antibody concentrations among sexes, males seem to present higher concentrations, but this is not statistically significant and comes in contrast with the general acceptance that females typically develop higher immune responses to viral infections and vaccines [ 42 ]. However, comparing the concentrations among sexes per age group, males presented statistically significantly higher concentration in the younger age group “25–54”, a finding also supported by another study [ 43 ]. In any case, both sexes showed high antibody concentrations in all age groups, making them immune to measles.…”
Section: Discussionsupporting
confidence: 81%
“…Comparing the level of antibodies titer among the two sexes, males seems to present higher titer but it is not statistically significant and it comes in contrast with the general acceptance that females typically develop higher immune responses to viral infections and vaccine [38]. However, comparing the titer among sexes per age group, males present statistically significantly higher titer in younger age group "25-54", finding supported also by other study [39]. In any case, both sexes show high antibody titres in all age groups, making them immune to measles.…”
Section: Discussionsupporting
confidence: 50%
“…Different studies have demonstrated that there are gender differences in measles seroprevalence (Domínguez et al, 2006;Poethko-Müller & Mankertz, 2012;Kostinov et al, 2021;Mathew et al, 2022). Nevertheless, it is noteworthy that while some studies observed that male participants were more likely to have immunity against measles (Kostinov et al, 2021;Mathew et al, 2022), others found male participants more likely to be seronegative (Poethko-Müller& Mankertz, 2012).…”
Section: Discussionmentioning
confidence: 99%